Risk of thrombosis with thrombocytopenia syndrome after COVID‐19 vaccination prior to the recognition of vaccine‐induced thrombocytopenia and thrombosis: A self‐controlled case series study in England. Issue 3 (20th April 2022) - Higgins, Hannah; Andrews, Nick; Stowe, Julia; Amirthalingam, Gayatri; Ramsay, Mary; Bahra, Gurpreet; Hackett, Anthony; Breen, Karen A.; Desborough, Michael; Khan, Dalia; Leary, Heather; Sweeney, Connor; et al.
Abstract: Background: Several studies have found increased risks of thrombosis with thrombocytopenia syndrome (TTS) following the ChAdOx1 vaccination. However, case ascertainment is often incomplete in large electronic health record (EHR)‐based studies. Objectives: To assess for an association between clinically validated TTS and COVID‐19 vaccination. Methods: We used the self‐controlled case series method to assess the risks of clinically validated acute TTS after a first COVID‐19 vaccine dose (BNT162b2 or ChAdOx1) or severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Case ascertainment was performed uninformed of vaccination status via a retrospective clinical review of hospital EHR systems, including active ascertainment of thrombocytopenia. Results: One hundred seventy individuals were admitted to the hospital for a TTS event at the study sites between January 1 and March 31, 2021. A significant increased risk (relative incidence [RI], 5.67; 95% confidence interval [CI], 1.02‐31.38) of TTS 4 to 27 days after ChAdOx1 was observed in the youngest age group (18‐ to 39‐year‐olds). No other period had a significant increase, although for ChAdOx1 for all ages combined the RI was >1 in the 4‐ to 27‐ and 28‐ to 41‐day periods (RI, 1.52; 95% CI, 0.88‐2.63; and (RI, 1.70; 95% CI, 0.73‐3.8, respectively). There was no significant increased risk of TTS after BNT162b2 in any period. Increased risks of TTS following a positive SARS‐CoV‐2 test occurred across all age groups and exposure periods. Conclusions: We demonstrate an increased risk of TTS in the 4 to 27 days following COVID‐19 vaccination, particularly for ChAdOx1. These risks were lower than following SARS‐CoV‐2 infection. An alternative vaccine may be preferable in younger age groups in whom the risk of postvaccine TTS is greatest.